Persepsi Mahasiswa Akuntansi terhadap Etika Profesi Sebagai Calon Akuntan di Universitas 17 Agustus 1945 Surabaya - Sevira Pahlevi Santoso; Hwihanus Hwihanus (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to explore accounting students' perceptions of professional ethics at the University of 17 August 1945 Surabaya. Professional ethics is an important foundation for accountants in carrying out their activities professionally. Using qualitative methods with in-depth interviews, this research examines the understanding, attitudes and factors that influence students' perceptions of the importance of ethics in the world of accounting. It is hoped that the research results will provide new insight into accounting students' ethical awareness and the challenges they face in implementing professional ethics. In addition, research finds that ethical perceptions have a positive impact on accounting students' decision-making behavior, where they tend to choose actions that are in accordance with ethical values ​​in facing challenges. This research recommends increased integration of ethics education in the curriculum and the need for further research on the impact of organizational culture on students' ethical behavior in the world of work.